Cost-effectiveness of apixaban vs warfarin for secondary stroke prevention in atrial fibrillation - Kamel, Hooman (Lippincott Williams & Wilkins, 2012)
OBJECTIVE: To compare the cost-effectiveness of apixaban vs warfarin for secondary stroke prevention in patients with atrial fibrillation (AF). METHODS: Using standard methods, we created a Markov decision model based on the estimated cost of apixaban and data from the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE) trial and other trials of warfarin therapy for AF. We quantified the cost and quality-adjusted life expectancy resulting from apixaban 5 mg twice daily compared with those from warfarin therapy targeted to an international normalized ratio of 2–3. Our base case population was a cohort of 70-year-old patients with no contraindication to anticoagulation and a history of stroke or TIA from nonvalvular AF. RESULTS: Warfarin therapy resulted in a quality-adjusted life expectancy of 3.91 years at a cost of $378,500. In comparison, treatment with apixaban led to a quality-adjusted life expectancy of 4.19 years at a cost of $381,700. Therefore, apixaban provided a gain of 0.28 quality-adjusted life-years (QALYs) at an additional cost of $3,200, resulting in an incremental cost-effectiveness ratio of $11,400 per QALY. Our findings were robust in univariate sensitivity analyses varying model inputs across plausible ranges. In Monte Carlo analysis, apixaban was cost-effective in 62% of simulations using a threshold of $50,000 per QALY and 81% of simulations using a threshold of $100,000 per QALY. CONCLUSIONS: Apixaban appears to be cost-effective relative to warfarin for secondary stroke prevention in patients with AF, assuming that it is introduced at a price similar to that of dabigatran.